The design of nonlinear damped building isolation systems by using mobility analysis - Zhu, Yun-Peng; Lang, Z. Q.; Fujita, Kohei; Takewaki, Izuru (Frontiers in Built Environment, 2022)
Additional power law nonlinear damping has shown advantages in seismic isolation of buildings. The design of nonlinear damped building isolation systems can be conducted in the frequency domain based on the Output Frequency Response Function (OFRF) of the building’s frequency output responses. But this often requires many runs of simulations of nonlinear building systems, which will spend long time when the Finite Element (FE) model or differential equation model of the building system is complex. In this study, the issue will be resolved by an integrated mobility analysis and equivalent linearization approach. In this approach, the complex linear building system without additional nonlinear damping is represented by several data-driven AutoRegressive with eXogenous input (ARX) models. Mobilities of the building system can be evaluated from these ARX models, so that a mobility based frequency domain representation of the linear building system can be achieved. After that, equivalent linearization approach is applied to simulate the building system with additional nonlinear damping. Finally, the OFRF based design can be conducted based on the proposed mobility analysis and equivalent linearization approach. A 4-Degree of Freedom (DoF) building system is discussed to demonstrate the advantages of the proposed method. The results indicate that the new approach can significantly increase the efficiency of the design and be effectively applied to the design of complex nonlinear building isolation systems.